Design and analysis of frequency reconfigurable antenna for global positioning system applications - Najim Abdallah Jazea; Ali Khalid Jassim; Alaa Kareem Hassan (Bulletin of Electrical Engineering and Informatics, 2022)
A compact frequency reconfigurable antenna is designed and analyzed in this paper to operate with global positioning system (GPS) and worldwide interoperability for microwave access (WiMAX) applications. The designed antenna is printed on flame resistant 4 (FR4) epoxy substrate with relative permittivity is 4.3, loss tangent of 0.03 and overall substrate with ground (GND) plane dimensions of (54.6x54.6x1.6) mm3 and patch dimensions of (45x45) mm2. The antenna is designed and optimized using computer simulation technology (CST) package through series of parametric studies in order to cover the GPS, WiMAX bands with resonant frequency of 1.229 GHz, 1.575 GHz, and 3.34 GHz. Two triangular slots at the patch sides and single elliptical slot at the middle are etched for the best antenna performance. The designed antenna performs frequency re-configurability by using PIN diode switch at the inset feed to change the operating frequencies from double band operation at (1.575 and 3.34) GHz to single band at 1.229 GHz under S11 ≤-10 dB. The proposed antenna produces accepted simulation results with voltage standing wave ratio (VSWR), maximum radiation efficiency and gain of less than 2.76% and 7.035 dBi respectively.